2017
DOI: 10.1590/s2179-975x4017
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community in the last undammed stretch of the Paraná River: considerations on the distance from the dam

Abstract: Aim: To evaluate the influence of upstream reservoirs on the temporal and spatial variation of the phytoplankton community in the Paraná River channel and the importance of its main tributaries in reducing the oligotrophication process along this stretch of the river. Materials and Methods Sampling of phytoplankton and physical and chemical variables was performed quarterly between August 2013 and May 2015, in the Paraná River main channel and in the mouth of the main tributaries, at the stretch located betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The construction of reservoirs disrupts the longitudinal gradient of rivers and causes conspicuous upstream physical and chemical modifications, including the attenuation of downstream flood pulses (Stanford & Ward, 2001;Jati et al, 2017a). In addition, they are prone to nutrient enrichment, which often causes the proliferation of potentially harmful algal blooms, such as those of Cyanobacteria, compromising ecosystem services such as multiple water uses (Akhurst et al, 2017;Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The construction of reservoirs disrupts the longitudinal gradient of rivers and causes conspicuous upstream physical and chemical modifications, including the attenuation of downstream flood pulses (Stanford & Ward, 2001;Jati et al, 2017a). In addition, they are prone to nutrient enrichment, which often causes the proliferation of potentially harmful algal blooms, such as those of Cyanobacteria, compromising ecosystem services such as multiple water uses (Akhurst et al, 2017;Marques et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rychteck and Znachor (2011) also observed that the spatial heterogeneity of phytoplankton in the Římov Reservoir of the Czech Republic was most clear in the wet season, reflecting obvious gradients of environmental parameters extending from the river to the dam, consistent with our results. Finally, Jati et al (2017) observed the disappearance of rapids caused by damming in the Paraná River led to decreased seasonal differences in phytoplankton species richness.…”
Section: Discussionmentioning
confidence: 99%
“…also observed that the spatial heterogeneity of phytoplankton in the Římov Reservoir of the Czech Republic was most clear in the wet season, reflecting obvious gradients of environmental parameters extending from the river to the dam, consistent with our results. Finally,Jati et al (2017) observed the disappearance of rapids caused by damming in the Paraná River led to decreased seasonal differences in phytoplankton species richness.5 | CONCLUSIONSThis study was conducted in subtropical rivers with 13 ladder dams in the main river channel, investigated the correlation between seasonal and spatial distribution characteristics of environmental factors and species richness, and tested the prediction of SDC. The results showed that the construction of cascade dams enhanced the spatial differences in phytoplankton species richness, especially during wet periods.…”
mentioning
confidence: 92%